2010
DOI: 10.2147/cpaa.s11262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of antimicrobial lock solutions used in a treatment modality: a retrospective case series analysis

Abstract: BackgroundAntimicrobial lock therapy (ALT) may be considered as adjunctive therapy in the treatment of catheter-related bloodstream infections (CRBSI) when catheter removal is not a favorable option.ObjectiveTo evaluate the outcomes associated with ALT as adjunctive treatment of CRBSI.MethodsThis was a 24-month retrospective case series analysis evaluating patients treated for more than 24 hours with ALT. The primary outcome was blood culture sterilization for 30 days posttherapy. The impact of ALT duration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 31 publications
1
18
0
6
Order By: Relevance
“…Gentamicin ALT is typically administered at 2.5 or 5 mg/ml concentrations [23]. However, data about its efficacy are contradictory, as Lee et al [24] showed that it was not effective over 5 days of ALT in in vitro biofilm models, nor were cefazolin, nafcillin or erythromycin, while Fernandez-Hidalgo et al [25] found that gentamicin ALT was generally effective on S. aureus biofilms in rabbit catheters.…”
Section: Aminoglycosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Gentamicin ALT is typically administered at 2.5 or 5 mg/ml concentrations [23]. However, data about its efficacy are contradictory, as Lee et al [24] showed that it was not effective over 5 days of ALT in in vitro biofilm models, nor were cefazolin, nafcillin or erythromycin, while Fernandez-Hidalgo et al [25] found that gentamicin ALT was generally effective on S. aureus biofilms in rabbit catheters.…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…Duration of locks varies from 3 to 27 days and ALT is generally associated with systemic treatment [6]. Indeed, Bookstaver et al [23] showed that active systemic therapy, associated with vancomycin ALT, alone or together with gentamicin or ethanol, allowed good success rates while avoiding catheter removal.…”
Section: Vancomycin Lock Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This [11] found DPT systemic and lock therapy to be effective in 11 of 13 patients with CRBSI. Bookstaver et al [12] reported the efficacy of systemic and lock therapy in 26 patients with Gram-positive catheter-related infections using different antibiotics. In particular, DPT was used in six patients, always successfully.…”
Section: Discussionmentioning
confidence: 99%
“…excelsiormedical.com). Furthermore, recent studies have shown a benefit from ELT in treating and preventing CRBIs (Bookstaver et al, 2010;Broom et al, 2009;Cober et al, 2011;Mouw et al, 2008;Sanders et al, 2008). As a result of broad interest in ELT at the Nebraska Medical Center, Maiefski et al (2009) devised ELT recommendations for prevention and treatment of CRBSI based on the findings in their review.…”
Section: Ethanol- Edta-and Levofloxacin-based Clsmentioning
confidence: 99%